The Impact of Non-Andrological Medications on Semen Characteristics, Oxidative Stress and Inflammatory Parameters - Gerardo Salerno; Marina Borro; Vincenzo Visco; Soraya Olana; Francesca Gargano; Salvatore Raffa; Virginia Zamponi; Camilla Mancini; Antongiulio Faggiano; Maurizio Simmaco; Rossella Mazzilli (Medicina, 2023)
Background and Objectives: The aim of this study was to evaluate the impact of medications on oxidative stress, inflammatory biomarkers and semen characteristics in males with idiopathic infertility. Materials and Methods: In this observational case-control clinical study, 50 men with idiopathic infertility were enrolled, of whom 38 (the study group) were on pharmacological treatment and 12 made up the control group. The study group was clustered according to the medications (Group A: anti-hypertensive, n = 10; Group B: thyroxine, n = 6; Group C: non-steroidal anti-inflammatory drugs, n = 13; Group D: miscellaneous, n = 6; Group E: lipid-lowering drugs, n = 4). Semen analyses were performed according to WHO 2010 guidelines. Interleukins (IL)-10, IL-1 beta, IL-4, IL-6, Tumor Necrosis Factor- alpha (TNF-alpha) and IL-1 alpha were determined using a solid-phase sandwich immunoassay. The diacron reactive oxygen metabolites, d-ROMs test, was performed by means of a colorimetric determination of reactive oxygen metabolites and measured with a spectrophotometer. Beta-2-microglobulin and cystatin-C were measured with an immunoturbidimetric analyzer. Results: No differences between the study and control groups for age and macroscopic and microscopic semen characteristics were found, nor were any differences found after clustering according to the drug categories. IL-1 alpha and IL-10 were significantly lower in the study group compared with the control group; IL-10 was significantly lower in groups A, B, C and D compared with the control group. Furthermore, a direct correlation between IL-1 alpha, IL-10 and TNF-alpha and leukocytes was found. Conclusions: Despite the sample size limitations, the data suggest a correlation between drug use and activation of the inflammatory response. This could clarify the pathogenic mechanism of action for several pharmacological classes on male infertility.